Community asset participation and social medicine increases qualities of life. (August 2020) - Munford, Luke A.; Panagioti, Maria; Bower, Peter; Skevington, Suzanne M.
Abstract: Rationale: Social prescribing to community assets, like social groups, is a current policy goal. As aging adults lead longer, healthier lives, the effects of participating in community assets raises questions about whether subjective quality of life (QoL) improves during participation and on what dimensions. Objective: The study's goal was to examine the effectiveness of community assets at improving QoL among older people living in the community. Method: Examining longitudinal survey data which tracked health and wellbeing in older adults living in Salford, UK over 12 months, we first used regressions on community assets to compare the World Health Organization's QoL Assessment (WHOQOL-BREF) domains at baseline for those who already participated in community assets (54%) and with non-participants (46%). Second, we used propensity score matching to compare QoL in an 'uptake' group (no initial participation but who participated at 12 months), to those who never participated, and to a 'cessation' group who participated initially, but ceased within one year, to those who always participated. Results: Group comparisons confirmed that participants reported significantly higher QoL on all domains – environmental, psychological, physical, and social QoL – and on 16 predicted facets. After affirming group matching reliability, the strongest results were for the uptake group, with significant improvements in all domains, and in 18 facets. All QoL domains decreased in the cessation group, but overall, the effect was weaker. As predicted from the context, QoL relating to 'opportunities for recreation and leisure' showed the greatest effect. Furthermore, QoL increased with uptake, and decreased with cessation. Conclusion: Policies to improve QoL in later life should be designed not just to promote community assets, but also maintain participation once initiated. Highlights: Social prescribing to community assets such as social groups is now a policy goal. Little is known about their effect on participants' quality of life (QoL). Community asset participants reported higher QoL on all four domains. Participation uptake strongly led to increased QoL. Cessation was detrimental to QoL.